2008
DOI: 10.1038/nature06512
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in a long-term experiment with a plankton community

Abstract: Mathematical models predict that species interactions such as competition and predation can generate chaos. However, experimental demonstrations of chaos in ecology are scarce, and have been limited to simple laboratory systems with a short duration and artificial species combinations. Here, we present the first experimental demonstration of chaos in a long-term experiment with a complex food web. Our food web was isolated from the Baltic Sea, and consisted of bacteria, several phytoplankton species, herbivoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
374
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(391 citation statements)
references
References 24 publications
13
374
2
2
Order By: Relevance
“…This suggests that there is no unifying environmental selection across the group of microcosms; rather, the complex dynamics caused by community-environment feedbacks and interspecies interactions, and/or stochastic effects, create different selective environments in replicate microcosms. In our microcosms, metabolic feedbacks may lead to non-linear ecosystem dynamics, potentially producing chaotic or initial condition-dependent trajectories as observed in other studies (Becks et al, 2005;Graham et al, 2007;Benincà et al, 2008). Indirect interspecies interactions mediated by the physical environment are also likely to have a key role in our microcosms: for example, the generation of an anaerobic state as a result of cellulose degradation and sulphate reduction, which will strengthen selection for anaerobes in the developing community.…”
Section: Predictability Of Microbial Ecosystem Developmentmentioning
confidence: 91%
“…This suggests that there is no unifying environmental selection across the group of microcosms; rather, the complex dynamics caused by community-environment feedbacks and interspecies interactions, and/or stochastic effects, create different selective environments in replicate microcosms. In our microcosms, metabolic feedbacks may lead to non-linear ecosystem dynamics, potentially producing chaotic or initial condition-dependent trajectories as observed in other studies (Becks et al, 2005;Graham et al, 2007;Benincà et al, 2008). Indirect interspecies interactions mediated by the physical environment are also likely to have a key role in our microcosms: for example, the generation of an anaerobic state as a result of cellulose degradation and sulphate reduction, which will strengthen selection for anaerobes in the developing community.…”
Section: Predictability Of Microbial Ecosystem Developmentmentioning
confidence: 91%
“…Despite sometimes major fluctuations in species numbers, when a species became dominant, other species at low numbers bounced back, though at different rates. Later empirical work eloquently demonstrated that these predictions may actually occur in reality (Benincà et al 2008). In a laboratory setup with a plankton community in tanks many different species coexisted for a period up to 2300 days, covering a couple of hundred generations.…”
Section: Coexistence Mechanisms May Results In Unpredictable Dynamicsmentioning
confidence: 99%
“…However, in a relatively stable environment, competitive equivalence among species, as assumed in neutral theory, can lead to overall predictable community patterns (long-term co-occurrence). Finally, the plankton example shows the reverse, where predictable species replacements result in chaotic dynamics of a community which is as unpredictable as the weather (Benincà et al 2008). These contrasts feed the uneasy relationship that ecology has with deterministic versus stochastic processes underlying the structure of ecological communities (Bjørnstad 2015;Chase and Myers 2011;Vellend et al 2014).…”
Section: Conclusion: the Interplay Between Scale-dependent Predictablmentioning
confidence: 96%
“…The high number of interacting species in nature and the resulting potential of complex dynamics and chaos are of interest, because these complex dynamics are suggested to maintain biodiversity 17 and limit our ability for long-term predictions 18 . Although chaotic dynamics have not been reported for natural populations, there is now accumulating evidence from laboratory studies [18][19][20] and theory [21][22][23][24] underlining the potential role of chaos.…”
mentioning
confidence: 99%
“…Although chaotic dynamics have not been reported for natural populations, there is now accumulating evidence from laboratory studies [18][19][20] and theory [21][22][23][24] underlining the potential role of chaos. In trying to understand the meaning of chaos for population dynamics, it is necessary to critically evaluate theoretical predictions by manipulative experiments and compare it with systems with cyclic dynamics.…”
mentioning
confidence: 99%